Settlement land management based on land capability in Batu City - Rahmawati, Dessy Citra; Hasibuan, Hayati Sari; Setiawati, Sri (Journal of Degraded and Mining Lands Management, 2023)
Urban expansion occurs in big cities in Indonesia, including Batu City. An increase in the built-up area occurred in Batu City by 554.4 ha or 2.78%, and a decrease in agricultural land by 341.1 ha occurred in 2008-2018. If the Batu City government does not pay attention to the availability of environmental services or consider the geomorphological conditions of Batu City for developing settlements. In that case, it will have an environmental impact. The environmental problem in Batu City during the 2009-2019 period was an increase in greenhouse gases by 0.75% per year. Batu City is located in a hilly area. It is necessary to explore land capability in Batu City so that land use planning follows its environmental services and is sustainable. This study aimed to determine the land capability for settlements in Batu City based on the Regulation of the State Minister for the Environment Number 17 of 2009 concerning Guidelines for Determining Environmental Supporting Capacity in Regional Spatial Planning. This study used a geographic information system (GIS) and ArcGIS 10.8 software. The method used was overlapping soil texture, slope, drainage, effective soil depth, erosion, and flood potential maps. Batu City has a slope of 30-45% and a total area of 6,581.03 ha or 33% of the area of Batu City. The largest erosion rate reached 10,326.33 ha or 52% of the total area of Batu City. Erosion occurs on land used for agriculture or moorland. Soil protection and erosion control measures are strongly recommended. The area around Batu City, 1,174.28 ha, experienced considerable erosion, and 2,631.62 ha of land in Batu City is used for settlements. Land capability analysis can determine the starting point or basis for settlement land management in Batu City, which has a slope of more than 15%. There are only 461.9 ha of land management for settlement which follows the regional spatial planning and land capability in Batu City, spread over three different districts.